2005
DOI: 10.1027/1016-9040.10.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Risk Attitudes and Behavior Among Norwegian Adolescents

Abstract: Abstract. The core aim of the present study is to compare the effects of a safety campaign and a behavior modification program on traffic safety. As is the case in community-based health promotion, the present study's approach of the attitude campaign was based on active participation of the group of recipients. One of the reasons why many attitude campaigns conducted previously have failed may be that they have been society-based public health programs. Both the interventions were carried out simultaneously a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…These researchers argued that campaigns aimed at influencing safety attitudes in general had been unsuccessful as they did not focus on the specific attitudes likely to influence risk-taking behavior. Research has demonstrated that general attitudes are poor predictors of specific behaviors (Ajzen and Fishbein, 1991), such as unsafe driving (Iversen, 2004;Iversen et al, 2005). More specific attitudes towards risktaking behavior in driving can predict unsafe driving behavior, such as attitudes towards rule violations, joyriding, and speeding (Iversen, 2004;Ulleberg and Rundmo, 2002;West and Hall, 1997).…”
Section: Attitudes Towards Unsafe Drivingmentioning
confidence: 99%
See 4 more Smart Citations
“…These researchers argued that campaigns aimed at influencing safety attitudes in general had been unsuccessful as they did not focus on the specific attitudes likely to influence risk-taking behavior. Research has demonstrated that general attitudes are poor predictors of specific behaviors (Ajzen and Fishbein, 1991), such as unsafe driving (Iversen, 2004;Iversen et al, 2005). More specific attitudes towards risktaking behavior in driving can predict unsafe driving behavior, such as attitudes towards rule violations, joyriding, and speeding (Iversen, 2004;Ulleberg and Rundmo, 2002;West and Hall, 1997).…”
Section: Attitudes Towards Unsafe Drivingmentioning
confidence: 99%
“…More specific attitudes towards risktaking behavior in driving can predict unsafe driving behavior, such as attitudes towards rule violations, joyriding, and speeding (Iversen, 2004;Ulleberg and Rundmo, 2002;West and Hall, 1997). Research suggests that differences in attitudes towards traffic safety and selfreported driving behavior are only found when interventions target specific attitudes rather than general behavior modification (Iversen et al, 2005). This indicates that psychological interventions may be optimized when separated from skill and safety orientation programs (Lajunen and Summala, 1995).…”
Section: Attitudes Towards Unsafe Drivingmentioning
confidence: 99%
See 3 more Smart Citations